Quality of translation via google translate in comedy texts - Bania, Allif Syahputra; Faridy, Najihatul (Universitas Islam Negeri Banda Aceh, 2023)
A translation process of considerable quality should possess the ability to effectively communicate a clear and definite meaning from the source language to the target language. While Google Translate serves as a useful tool for comprehending translated textual content in a general sense, it is important to note that automated machines still possess inherent weaknesses and limitations. The translation of jokes within comedic texts, particularly in relation to language and cultural differences, proves to be a challenging task. This research was undertaken utilizing a qualitative-descriptive approach, with the bilingual comedy book titled